Does Capital Assistance and Financial Literacy Have an Impact on the Business Sustainability of MSMEs in Kediri City? - Srikalimah, Srikalimah; Munir, Miftahul (Jurnal Cendekia Keuangan, 2025)
Introduction/Main Objectives: Economic development in Kediri cannot be separated from the country's micro, small, and medium enterprises (MSMEs). Kediri MSMEs are promising businesses to develop because they can support economic development at the micro and macro levels. Background Problems: The problem MSME actors face in Kediri city is the lack of capital in their businesses. There is a gap in several studies because no one has directly examined the impact of capital assistance on three groups that receive capital assistance in Kediri City, namely the first is cigarette factory workers who have a business, the second is cigarette factory workers who have a business, and the third is entrepreneurs in the industrial and trade sectors. Novelty: Theoretical model of research on capital assistance and financial literacy on the sustainability of SMEs in the city of Kediri. Research Methods: The research approach used is a quantitative approach. The sampling technique used was a combination of stratified random sampling from Mojoroto sub-district, Kota sub-district, and Pesantren sub-district. Primary data collection was carried out on 100 respondents who received capital assistance in the city of Kediri. Finding/Results: Capital assistance has a significant effect on business sustainability. Financial literacy has a positive and significant effect on business sustainability. Capital assistance and financial literacy together have a positive and significant effect on business sustainability. Research limitation/implications: This study provides an overview that Kediri City MSME business actors who receive capital assistance , namely first, cigarette factory workers who have businesses, second, cigarette factory workers who have businesses, and third, entrepreneurs in the industrial and trade sectors can use capital assistance wisely supported by financial literacy obtained from financial management training provided by the government or the existing MSME community.